2015
DOI: 10.1016/j.jsps.2015.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Safety of lacosamide in children with refractory partial epilepsy

Abstract: Lacosamide is a well-tolerated newer antiepileptic drug that is effective in refractory partial epilepsy paediatric patients and concurrently improved patient's behaviour.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…62 In a study by Pasha et al, behaviour was evaluated objectively, and was shown to have improved after 3 months' treatment with LCM. 26 A case of a 5-year old girl who developed behavioural problems after taking LCM (100 mg/day for 1 week) was also reported by the same group. 25 After persisting with treatment for 4 weeks, LCM was stopped and the child's behaviour returned to 'normal'.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…62 In a study by Pasha et al, behaviour was evaluated objectively, and was shown to have improved after 3 months' treatment with LCM. 26 A case of a 5-year old girl who developed behavioural problems after taking LCM (100 mg/day for 1 week) was also reported by the same group. 25 After persisting with treatment for 4 weeks, LCM was stopped and the child's behaviour returned to 'normal'.…”
Section: Discussionmentioning
confidence: 68%
“…25 The authors also assessed behaviour using the Conners Comprehensive Behaviour Rating Scale. 26 The score was 48.04 ± 10.57 at baseline and 19.27 ± 8.03 after 3 months' treatment with LCM, representing a statistically significant improvement in behaviour. The significant reduction in seizure frequency during the study may have contributed to the improvement in behaviour.…”
Section: Safety Outcomesmentioning
confidence: 86%
“…Refractory seizurePasha et al41 An open label, hospital-based study confirmed the usefulness of lacosamide for adjuvant treatment in patients with refractory partial epilepsy…”
mentioning
confidence: 92%
“…It is relatively well-tolerated. Common side effects include dizziness, headache, nausea, vertigo, somnolence, ataxia, and, in a small number of patients, a prolongation of the PR interval and atrioventricular block on electrocardiography [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%